2007
DOI: 10.1016/j.brainresbull.2006.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Rhodamine backfilling and confocal microscopy as a tool for the unambiguous identification of neuronal cell types: A study of the neurones of the rat cochlear nucleus

Abstract: Adequate interpretation of the functional data characterising the projection neurones of the cochlear nucleus (CN) is impossible without the unequivocal classification of these cell types at the end of the experiments. In this study, morphological criteria applicable for unambiguous identification of CN neurones have been sought. The neurones were labelled with rhodamine from incisions severing the projection pathways of the individual cell types, allowing their selective labelling and morphological characteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The presence of labeled thick fibers that curve around the inferior cerebellar peduncle and circumvent the spinal tract of the trigeminal nerve is compatible with the intermediate acoustic stria (IAS; Figure 2B; Smith et al, 2005). Retrogradely labeled neurons were found in the PVCN with a clear contralateral predominance (Figure 2B), and they were readily identified as octopus cells based on their distinct dendritic shape (Figure 2C; Harrison and Irving, 1966; Saldaña et al, 1987; Pocsai et al, 2007; Bazwinsky et al, 2008). These cells had large, irregularly shaped cell bodies (~ 20 μm in diameter) with three to five thick primary dendrites emerging from only one side of the cell body (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…The presence of labeled thick fibers that curve around the inferior cerebellar peduncle and circumvent the spinal tract of the trigeminal nerve is compatible with the intermediate acoustic stria (IAS; Figure 2B; Smith et al, 2005). Retrogradely labeled neurons were found in the PVCN with a clear contralateral predominance (Figure 2B), and they were readily identified as octopus cells based on their distinct dendritic shape (Figure 2C; Harrison and Irving, 1966; Saldaña et al, 1987; Pocsai et al, 2007; Bazwinsky et al, 2008). These cells had large, irregularly shaped cell bodies (~ 20 μm in diameter) with three to five thick primary dendrites emerging from only one side of the cell body (Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Bushy cells typically have one or two primary dendrites. Two dendritic processes usually originate from the opposite poles of the cell body and proceed away from each other (Paolini and Clark, 1998; Pocsai et al, 2007). The dendrites of bushy cells characteristically end in a spray of thinner and shorter braches.…”
Section: Introductionmentioning
confidence: 99%
“…Varieties of culture conditions for dissociated cell culture of C.N. on extracellular matrix compounds and biomaterials describing neuron morphology as well as setups for electrophysiological studies have been reported 15–19…”
Section: Introductionmentioning
confidence: 99%